2022
DOI: 10.3390/buildings12020145
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of BIM in RFI in Building Projects

Abstract: Requests for information (RFIs) are frequently used by the architecture, engineering, construction, and operation (AECO) industry to resolve doubts and inaccuracies and to request complimentary information. However, they can be inefficient due to the lag between issuance and response, generating delays and cost overruns. The building information modeling (BIM) methodology allows for the integration of information by using virtual models and facilitating the control and management of RFIs; however, the full pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A typical construction project will involve numerous requests for information (RFIs) that can be time-consuming and expensive (Morales et al, 2022). However, with the use of BIM, the number of RFIs can be greatly reduced (Toan et al, 2022;Zakeri et al, 2023).…”
Section: Requests For Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical construction project will involve numerous requests for information (RFIs) that can be time-consuming and expensive (Morales et al, 2022). However, with the use of BIM, the number of RFIs can be greatly reduced (Toan et al, 2022;Zakeri et al, 2023).…”
Section: Requests For Informationmentioning
confidence: 99%
“…Abdelbary et al (2020) analysed several case studies and found that the use of BIM had reduced the number of RFIs by 90%. With all project data available in one place, the project team can respond to RFIs quickly and accurately, reducing time and costs (Morales et al, 2022). Furthermore, BIM can make it easier to track RFIs and ensure timely resolution, which can help prevent delays and keep projects on schedule.…”
Section: Requests For Informationmentioning
confidence: 99%
“…BIM tools also grant a proper platform for implementing additional features for performance assessment into a building model [69]. Table A4 (as shown in Appendix A) shows the recent work performed in BIM, especially in buildings [70][71][72][73][74][75][76][77][78].…”
Section: Building Information Modeling (Bim)mentioning
confidence: 99%